Kinerja Teknik Pengomposan Limbah Tandan Kosong Sawit Menggunakan Metode Windrow Aerob Ditinjau Dari Rasio C/N - Adinda Ryvania Abrir; Adrianto Ahmad; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The palm oil industry is currently experiencing very rapid development which is marked by the increase of CPO production resulting the increase of waste product. The main solid waste from the palm oil industry is Empty Fruit Bunch (EFB) that contains high organic matter which has an impact on environmental pollution if not handled well. The composting process is one of the alternative method to reducing environmental pollution caused by waste EFB. However, the composting process takes a long time. Therefore, it is important to do a breakthrough to speed up the processing time. In this research, EFB composting process is done by adding a mixed culture that is useful as a starter and POME as a nutrition source. The purpose of this research was to determine the effect of adding POME toward C/N ratio in the windrow aerob composting. In composting process takes place with variations by adding POME 0%, 20%, 30%, and 40%. Treatment with addition of 30% POME showed the best result with the value of C/N ratio was 11.66 with a pH of 6.98, a temperature of 32.33C and a moisture content of 40.6%. with 25 days period of time. The conclusion of this research is that the addition of POME has an effect on reducing the C/N ratio and accelerating composting time.Keywords: Composting Process, C/N Ratio, Empty Fruit Bunch, Palm Oil MillEffluent (POME), Windrow